The Carnegie Tech Management Game: A Learning Experience in Production Management - Cangelosi, Vincent E. (Academy of Management Journal, 1965)
The article discusses the usefulness of games in teaching aspects of the production function. In examining this issue, the study tried to understand the level of attention paid to the production function in a management game situation and to measure the learning experience of the production manager within that game. The study focuses on a simulation exercise undertaken at the Carnegie Institute of Technology where two teams of packaged detergent industries were formed. The methodology, game activities, and conclusions are presented. The study found that the game simulated realistic production scheduling, production costs, short- and long-run strategies, but did not offer a distinct advantage to those students participating in the game over and above other students.